Optimization of synthesis a new composite of nano-MgO, CNT and Graphite as a catalyst in heterogeneous catalytic ozonation for the treatment of pesticide-laden wastewater. (February 2020) - Asgari, Ghorban; Seidmohammadi, Abdolmotaleb; Faradmal, Javad; Esrafili, Ali; Noori Sepehr, Mohammad; Jafarinia, Maghsoud
Graphical abstract: Highlights: Based on the extreme vertices mixture design (EVMD), 9 nano-MgO/CNT/Graphite composites were synthesized. All synthesized nano-MgO/CNT/Graphite composites were used as a catalyst in COP. The optimum catalyst was selected by using Minitab 17 and Design Expert 7. The optimum nano-MgO/CNT/Graphite composite exhibited high activity and stability towards COP. The nano-MgO/CNT/Graphite was easily and quickly separated by sedimentation after each run. Abstract: The production of an efficient, reusable, stable and easily separable catalyst in the ozonation process through a reliable procedure is one of the essential requirements of the catalytic ozonation process (COP). In this study, the nano-MgO/CNT/Graphite composite was synthesized to use as a new catalyst in the COP. Synthesis of the nano-MgO/CNT/Graphite was carried out based on the extreme vertices mixture design (EVMD) using three components; MgO nanoparticles, carbon nanotubes (CNTs) and Graphite. Based on EVMD, 9 compositions were produced. For assessing the catalytic activity of synthesized compositions, pesticide manufacturing plant wastewater (PMPW) (initial COD=617 mg/L and TOC = 121) was treated in COP with new synthesized catalytic. The highest COD and TOC removal and destruction efficiencies were attained with composition C-9. The surface area of the optimum nano-MgO/CNT/Graphite was calculated to be had 221.631 m 2 g −1 and a high density of basic surface functional groups. Kinetics of PMPW oxidation indicated that the rate of COD and TOC removal efficiencies in the optimum nano-MgO/CNT/Graphite/O3 process were 12.73 (13.24/1.04 mg COD/L.min) and 7.11 (1.44/0.2 mg TOC/L.min) times as high as those in the single ozonation (SOP), respectively. Clearly, the optimum nano-MgO/CNT/Graphite showed a significant ability in catalysis of the ozonation process of organic materials by means of increasing O3 decomposition and OH production. The synthesized optimum nano-MgO/CNT/Graphite was reusable because of the stability and durability of the catalytic activities.